A Note on Professor Solow's Growth Model - Buttrick, John (Quarterly Journal of Economics, 1958)
In February 1956 issue of this Journal, Robert M. Solow presented an ingeniously simple yet extremely useful model for examination of various aspects of problem of economic growth.1 It does not seem to be generally realized, however, that this model, after a minor change, may be used to make sense out of assertions that: (a) a large initial dose of investment may be required before an underdeveloped country can overcome existing barriers to growth; (b) it may pay to adopt capital-intensive production methods even if they appear to be noneconomic; (c) in contrast to (a) above, something very like spontaneous combustion sometimes occurs, i.e., for no apparent reason growth process becomes self-perpetuating. This feature of model may be used as an important element in an explanation of the industrial revolution. To proceed with argument, let me first reproduce Solow's equation (6): r = sF(r,1) nr